Maximtun ionization cross section of atoms - Tiwari P.; Rai D.K.; Rustgi M.L. (My University, 2025)
Various theoretical approaches for estimation of maximum ionization cross sections have been discussed and three new relations have been developed and used to evaluate maximum cross sections. Mann's calculations have been critically examined, and the present results have been compared with available experimental results.